Onerunka longi, a new genus and species of Thanerocleridae (Coleoptera) from Papua New Guinea, with systematic notes on the tribe Thaneroclerini - Kolibáč, Jiří (Zootaxa, 2012)
Onerunka longi n. gen., n. sp., a new member of Thanerocleridae (Thaneroclerinae: Thaneroclerini) is described from Papua New Guinea. The new genus is geographically isolated and morphologically distinct. It is probably related to Viticlerus Miyatake, 1977 from Fiji and Neoclerus Lewis, 1892 from south-eastern Asia. The tribe Viticlerini Winkler, 1982 is synonymized with Thaneroclerini Chapin, 1924.